Introductory programming in higher education: A systematic literature review - Rodrigues, Gabryella (2022)
A systematic literature review was performed on 33 papers obtained from the ACM, IEEE and Sciencedirect databases, in order to understand in depth, the introductory programming discipline (CS1) in higher education. Recently published works have been covered, providing an overview of the teaching-learning process of introductory programming and enabling to find out whether the research developed by universities worldwide is in line with the proposals made by ACM/IEEE-CS group for computer courses, regarding the transition to the competency-based model. The results show that the new techniques/technologies currently used in software development, as an example of agile methodology, has influenced the teaching-learning process of CS1 together with methods such as visual programming and e-learning. The analyzed papers discuss the importance of developing not only technical, but also social skills, corroborating that methodologies used in introductory programming courses need to focus on preparing students for an increasingly competitive market, associating new skills with technical aspects.